2022
DOI: 10.1111/joim.13442
|View full text |Cite
|
Sign up to set email alerts
|

Changes in eicosapentaenoic acid and docosahexaenoic acid and risk of cardiovascular events and atrial fibrillation: A secondary analysis of the OMEMI trial

Abstract: Background. The cardiovascular benefit from n-3 polyunsaturated fatty acids (PUFAs) after acute myocardial infarction (AMI) is controversial, and the importance of serum eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) concentrations for clinical events is unclear.Objectives. To assess changes in EPA and DHA serum concentrations during n-3 PUFA supplementation and their association with incident cardiovascular events.Methods. In the OMEMI trial, elderly patients with a recent AMI were randomized to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…These damaged cellular components, including damaged mitochondrial DNA and membrane proteins, serve as damage-associated molecular patterns (DAMPs) that activate innate immune responses through the same pathways as pathogen-associated molecular patterns (PAMPs) 32 . However, not all studies of low dose MeHg exposure point to clear autoimmune responses in exposed individuals 33-35 , and there are noted beneficial effects of other nutrients contained within MeHg-contaminated fish and seafood, including polyunsaturated fatty acids (PUFAs) that support healthy brain development in infants and children 9,36 and cardiovascular protection to adults 37,38 . In addition, some communities have strong cultural connections to foodways centered on fish and seafood that should be considered in this cost benefit analysis 39 .…”
Section: Introductionmentioning
confidence: 99%
“…These damaged cellular components, including damaged mitochondrial DNA and membrane proteins, serve as damage-associated molecular patterns (DAMPs) that activate innate immune responses through the same pathways as pathogen-associated molecular patterns (PAMPs) 32 . However, not all studies of low dose MeHg exposure point to clear autoimmune responses in exposed individuals 33-35 , and there are noted beneficial effects of other nutrients contained within MeHg-contaminated fish and seafood, including polyunsaturated fatty acids (PUFAs) that support healthy brain development in infants and children 9,36 and cardiovascular protection to adults 37,38 . In addition, some communities have strong cultural connections to foodways centered on fish and seafood that should be considered in this cost benefit analysis 39 .…”
Section: Introductionmentioning
confidence: 99%
“…A secondary analysis of the OMEMI study showed that greater on-treatment increases in EPA levels were associated with lower risk of MACE (HR 0.86; 95 %CI 0.75, 0.99), the lowest risk being found in the top three quartiles of EPA increase (HR 0.39; 95 %CI 0.19, 0.79). Conversely, changes in DHA did not associate to CV outcomes (HR 0.84; 95 %CI 0.66, 1.06) [95]. Overall, as elsewhere reviewed, there may be a required threshold of EPA to be reached, namely 100 μg/mL, to achieve a clinical benefit [96].…”
Section: ω-3 Fatty Acidsmentioning
confidence: 83%
“…Conversely, there was no significant association with changes in DHA [95]. ω-3 FAs (as free fatty acids) cause acute atrial conduction slowing, suppress AF inducibility, at times enhancing atrial flutter inducibility.…”
Section: ω-3 Fatty Acidsmentioning
confidence: 85%
“…Results showed no reduction in clinical events, whereas 7.2% of patients in the omega-3 fatty acid group versus 4.0% in the corn oil group developed atrial fibrillation ( 208 ). A secondary analysis of the OMEMI trial showed that a greater increase in eicosapentaenoic acid during treatment was associated with a higher risk of first-onset AF ( 209 ).…”
Section: Clinical Significance Of Polyunsaturated Fatty Acidsmentioning
confidence: 99%